2023
DOI: 10.1302/2633-1462.43.bjo-2022-0136.r1
|View full text |Cite
|
Sign up to set email alerts
|

Oxford hip and knee scores deteriorate in patients awaiting lower limb arthroplasty during the COVID-19 pandemic and predict a health state ‘worse than death’

Abstract: AimsThe COVID-19 pandemic has caused unprecedented disruption to elective orthopaedic services. The primary objective of this study was to examine changes in functional scores in patients awaiting total hip arthroplasty (THA), total knee arthroplasty (TKA), and unicompartmental knee arthroplasty (UKA). Secondary objectives were to investigate differences between these groups and identify those in a health state ‘worse than death’ (WTD).MethodsIn this prospective cohort study, preoperative Oxford hip and knee s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…33 Although we found no difference in waiting times between deprivation quintiles, all patients in our region are waiting a long time for TJR (5.5 years in some cases) while enduring chronic pain and impaired mobility; therefore, a detrimental effect on physical and mental health is unsurprising. Overall, 39.2% of patients waiting for TJR were in a state WTD, higher than the figures reported by other authors, 6,8,34 demonstrating the impact of unacceptably long waiting lists. Prior to the COVID-19 pandemic, 19% and 12% of patients waiting for THA and TKA, respectively, had WTD health states.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…33 Although we found no difference in waiting times between deprivation quintiles, all patients in our region are waiting a long time for TJR (5.5 years in some cases) while enduring chronic pain and impaired mobility; therefore, a detrimental effect on physical and mental health is unsurprising. Overall, 39.2% of patients waiting for TJR were in a state WTD, higher than the figures reported by other authors, 6,8,34 demonstrating the impact of unacceptably long waiting lists. Prior to the COVID-19 pandemic, 19% and 12% of patients waiting for THA and TKA, respectively, had WTD health states.…”
Section: Discussionmentioning
confidence: 57%
“…8 During the COVID-19 pandemic, this increased to 22% and 35% of patients awaiting TKA and THA, respectively. 6 Similarly, Clark et al 34 in 2023 found that overall, 29% of 174 patients waiting for THA, TKA, and unicompartmental knee arthroplasty during the COVID-19 pandemic were in a state WTD. A significantly smaller proportion of the least deprived patients in our study were living in a state WTD (29.5%) compared to all other deprivation quintiles (41.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation